2020
DOI: 10.21203/rs.3.rs-63781/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electroceutically induced subthalamic high frequency oscillations and evoked compound activity may explain the mechanism of therapeutic stimulation in Parkinson's Disease

Abstract: Despite having remarkable utility in treating movement disorders, the lack of understanding of the underlying mechanisms of high-frequency deep brain stimulation (DBS) is a main challenge in choosing personalized stimulation parameters. Here we investigate the modulations in local field potentials induced by therapeutic and non-therapeutic electrical stimulation of the subthalamic nucleus (STN) in Parkinson’s disease patients undergoing DBS surgery. We find that therapeutic high-frequency stimulation (130-180 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 85 publications
(148 reference statements)
1
3
0
Order By: Relevance
“…26 To this end, evoked resonant neural activity 27 has recently been hypothesized to be a substrate of STN efferent-driven recurrent inhibition from GPe. 28,29 This interpretation would also be consistent with persistent pallidal synaptic inhibition at high frequencies described in this study, given that evoked resonant neural activity is a resilient signal which occurs at frequencies above 250 Hz.…”
Section: Frequency-dependent Modulation Of Inhibitory Projections To Dbs Targetssupporting
confidence: 86%
“…26 To this end, evoked resonant neural activity 27 has recently been hypothesized to be a substrate of STN efferent-driven recurrent inhibition from GPe. 28,29 This interpretation would also be consistent with persistent pallidal synaptic inhibition at high frequencies described in this study, given that evoked resonant neural activity is a resilient signal which occurs at frequencies above 250 Hz.…”
Section: Frequency-dependent Modulation Of Inhibitory Projections To Dbs Targetssupporting
confidence: 86%
“…A recent report has shown that the frequency of the oscillation changes between periods and the signal lacks the attractor dynamics at DBS frequency harmonics [16]. However, Awad et al [61] found that paired pulse stimulation induced shortterm facilitation suggesting resonant activity, and Ozturk et al [67] observed evoked activity was greater at 160 Hz STN stimulation compared to 180 Hz stimulation. Only STN DBS demonstrates the later, oscillatory signal suggesting specific circuitry components are likely responsible [17,18,63,68].…”
Section: Dlep Vs Ernamentioning
confidence: 99%
“…Any correlation between DLEPs and HFO could also be explained as one being the epiphenomenon of the other. However, Ozturk et al [67] reports that the HFO persists after DBS pulse artifact and evoked waveforms were removed using a template extraction filter, although HFO did not occur when stimulating the STN at 20 Hz. These results suggest HFOs and evoked potentials may be independent of each other.…”
Section: Mechanism Of Dlep Generationmentioning
confidence: 99%
“…There is mounting evidence that TBS renders change to the brain, but the way in which TBS directly influences neural signals is unknown. Human studies of invasive non-TBS stimulation paints a mixed picture: some evidence suggests neural responses will generally align with the stimulation frequency [ 18 , 19 ], while others have found that low-frequency responses can be readily observed even following high-frequency (>100 Hz) stimulation [ 20 , 21 ]. However, there is broader agreement that evoked responses to cortical stimulation are constrained by functional and structural architecture [ 20 , 22 25 ].…”
Section: Introductionmentioning
confidence: 99%